Serum Cortistatin Levels in Patients with Ocular Active and Ocular Inactive Behcet Disease - Balbaba, Mehmet; Ulas, Fatih; Postaci, Sevinc Arzu; Oz, Burak; Aydin, Suleyman (Taylor & Francis Inc, 2020)
Purpose: To evaluate serum cortistatin (CST) levels in patients with ocular active and ocular inactive Behcet disease (BD) and its relationship with disease activity. Methods: 24 BD patients with ocular active, 24 BD patients with ocular inactive patients and 24 healthy control subjects were included in the study. Results: In ocular active and ocular inactive BD patients and healthy control subjects, the mean serum CST levels were 4.38 +/- 1.63ng/ml, 5.46 +/- 1.81ng/ml and 7.56 +/- 1.73ng/ml, respectively. ESR, serum CRP, CST levels and NLR were significantly different between the groups (p < 0.001 for all). The CST levels were similar between ocular active and inactive BD patient groups (p = 0.197). ESR, CRP and NLR were significantly higher in ocular active BD patients compared to ocular inactive BD patients and healthy control subjects (p < 0.05 for all). Conclusion: Serum CST level was significantly lower in BD patients. CST may be a neuropeptide that plays a role in the pathogenesis of BD.
Keywords: Behcet disease; Behcet disease ocular attack score 24; cortistatin; C-reactive protein; erythrocyte sedimentation rate; neutrophil-lymphocyte ratio